THE EFFECT OF USING LITERARY AND NON LITERARY TEXTS THROUGH CRITICAL READING APPROACH ON READING COMPREHENSION OF THE ELEVENTH GRADERS OF SMK ARINDA PALEMBANG - despita despita (Journal of English Education, Literature and Linguistics, 2020)
Abstract This study is aimed to investigating whether there is a significant difference between the students’ reading comprehension achievement using literary text and non-literary text through critical reading approach, finding which of the two materials that is more effective in reading comprehension. To achieve this goal, the researcher carried out quantitative study. Two classes have been taken: experimental class one using literary text and experimental class two using non-literary text. There were two instruments used in this research: reading test and interview. The results of data analysis showed there was a significant difference of between the students’ reading achievement taught by literary text and those taught by non-literary text through critical reading approach. Then, literary text was more effective than non-literary text. Hypothesis test showed that T-value was higher than T-table (4.402 > 2,002). It can be concluded null-hypothesis is rejected. It can be inferred that literary text is better than non-literary text for encouraging students’ critical reading. Keywords: critical reading approach, literary text, non-literary text, reading comprehension.